IMPACT OF THE SECOND ABBASID ERA TURMOIL ON ABI HAIAN AL-TAWHAIDI - Faisal Al-Sadoon, Ibtihal Abdulkareem; Hasan, Raeed Hazim (Journal of Tikrit University for Humanities, 2018)
During the second Al-Abbasi period, the scientific movement witnessed a flourishing and flourishing witnessed not before or after this period, so that many of the writers considered this stage one of the most fertile Arab-Islamic cultural stages. Political fragmentation has had a great impact on that prosperity. Although many regions have left and independent Baghdad, these provinces have been the cause of this prosperity. They have not only been competing with each other in politics but have also been most competitive Despite the cultural prosperity, the impact of political, social and economic turmoil on many of the clients and writers of the era has been reflected. Among the most famous of these is Abu Hayyan al-Tawhidi, who joined his literature with a touch of sadness, which often resulted in barbarous him to pessimism and then to rebel against this miserable situation, which suffered is a group of writers of his time, and we will address this in our article – Insha'a Allah - to explain it all.